1992
DOI: 10.1515/bchm3.1992.373.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis by Liver Cells During Suppression of Intralysosomal Proteolysis

Abstract: The lysosomotropic agent chloroquine is widely used as a specific inhibitor of intralysosomal proteolysis in isolated hepatocytes. It was shown that in vitro chloroquine reversibly inhibited purified cathepsins H, B, L in concentrations less than those observed inside lysosomes in vivo. However, administration of high doses of chloroquine to rats (30 -50 mg/kg i.p. as a single or repeated injections) was followed by increased cathepsin D and cysteine proteinase activities, as well as other lysosomal enzymes. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It also reduces the expression of MHC II on Kupffer cells [99] . Besides its anti-inflammatory actions, chloroquine inhibits lysosomal degradation and produces lysosomal changes resembling that of lysosomal storage disease in a variety of cells, including macrophages [100,101] . Increased vacuolation and the accumulation of lysosomes were observed in AMC in response to the intraperitoneal administration of chloroquine in 1-d-old rats.…”
Section: Response To Drugsmentioning
confidence: 99%
“…It also reduces the expression of MHC II on Kupffer cells [99] . Besides its anti-inflammatory actions, chloroquine inhibits lysosomal degradation and produces lysosomal changes resembling that of lysosomal storage disease in a variety of cells, including macrophages [100,101] . Increased vacuolation and the accumulation of lysosomes were observed in AMC in response to the intraperitoneal administration of chloroquine in 1-d-old rats.…”
Section: Response To Drugsmentioning
confidence: 99%
“…According to Mauthe et al [52], this drug inhibits autophagic flux by decreasing autophagosome-lysosome fusion. It was demonstrated in vitro that CQ reversibly inhibits purified cathepsins H (CH), B (CB), and L (CL) at concentrations less than those observed inside lysosomes in vivo [53]. Chloroquine administration did not induce any changes of carbon particle phagocytosis by liver macrophages, modifications of fluid-phase ( 125 I-PVP) uptake, and receptor-mediated endocytosis ( 125 I-asialo-fetuin uptake).…”
Section: Chloroquinementioning
confidence: 99%
“…Mannan, which belongs to a class of immunomodulators of polysaccharide origin, has been shown to stimulate macrophages in vivo through its interaction with the mannose receptor . Polysaccharides, unlike statins, are natural stimulators of macrophages, which cause the macrophages to increase their endocytic activity . Following endocytosis, these branched polysaccharides have the capacity to activate LDL and scavenger receptors and increase the uptake of atherogenic LDL cholesterol, as well as other lipoproteins with modified chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Polysaccharides, unlike statins, are natural stimulators of macrophages, which cause the macrophages to increase their endocytic activity. [13,14] Following endocytosis, these branched polysaccharides have the capacity to activate LDL and scavenger receptors and increase the uptake of atherogenic LDL cholesterol, as well as other lipoproteins with modified chemical structures. It has also been suggested that excess cholesterol may potentially be removed from the atherosclerotic plaque by the activated macrophages.…”
Section: Introductionmentioning
confidence: 99%